Uncovering the biology of FTO - Yeo, Giles S.H. (Elsevier, 2012)
Genome-wide association studies have revealed that SNPs in the first intron of FTO (Fat mass and Obesity related) are robustly associated with body mass index and obesity. Subsequently, it has become clear that this association with body weight, and increasingly food intake, is replicable across multiple populations and different age groups. However, to date, no conclusive link has been made between the risk alleles and FTO expression or its physiological role. FTO deficiency leads to a complex phenotype including postnatal mortality and growth retardation, pointing to some fundamental developmental role. Yet, the weight of evidence from a number of animal models where FTO expression has been perturbed indicates some role for FTO in energy homoeostasis. In addition, emerging data points to a role for FTO in the sensing of nutrients. In this review, we explore the in vivo and in vitro evidence detailing FTO's different faces and discuss how these might link to the regulation of body weight.